Gestational Age Conformity between New Ballard Score and Last Menstrual Period in Newborn with Respiratory Distress Syndrome - Sakinah, Wulan Dwi; Primadi, Aris; Prajitno, Ihrul Prianza (Althea Medical Journal, 2016)
Background: Gestational age is required to determine diagnosis and optimal management of newborns. The gold standard for gestational age determination is the first day of last menstrual period (LMP). However, not all mothers remember their LMP. Another method for gestational age determination after birth is the New Ballard Score (NBS). This method measures gestational age using two main components, namely neorumuscular and physical maturity. In premature infants, surfactant deficiency leads to hypoxia which eventually leads to neuromuscular disorders. This situation may cause younger gestational age estimation when using NBS. The objective of this study was to analyze the conformity between NBS and LMP in determining gestational age in newborns with respiratory distress syndrome (RDS).Methods: A cross-sectional study was conducted on 35 newborns with RDS that were recorded in 2012 database in Dr. Hasan Sadikin General Hospital Bandung. Data on the date of birth, LMP, NBS soon after birth, sex, birth weight, type of delivery and diagnosis were collected and analyzed statistically using Wilcoxon test.Results: The study showed that there was a significant difference (p<0.05) between gestational age determination done using NBS soon after birth and LMP in newborns with RDS.Conclusions: Gestational age determination based on NBS soon after birth does not conform the LMP in newborns with RDS. [AMJ.2016;3(3):401â4]DOI: 10.15850/amj.v3n3.888